Materials Science Advanced Topics - Mastai, Yitzhak (IntechOpen, 2013)
Today modern materials science is a vibrant, emerging scientific discipline at the forefront of physics, chemistry, engineering, biology and medicine, and is becoming increasingly international in scope as demonstrated by emerging international and intercontinental collaborations and exchanges. The overall purpose of this book is to provide timely and in-depth coverage of selected advanced topics in materials science. Divided into five sections, this book provides the latest research developments in many aspects of materials science. This book is of interest to both fundamental research and also to practicing scientists and will prove invaluable to all chemical engineers, industrial chemists and students in industry and academia.